Bridging the Digital Divide: Challenges and Opportunities of ICT in Higher Education in Bangladesh - Kabir, Mohammad Humayun (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aims to assess the current state of Information and Communications Technology integration in higher education institutions in Bangladesh, identifying major challenges, disparities, and opportunities for creating an inclusive and competitive digital learning environment. Methodology: This study used a qualitative review method based on secondary data, including policy documents (Digital Bangladesh Vision 2021, National ICT Policy 2018), institutional reports, and research articles. Data were analyzed using thematic content analysis. Main Findings: Information and Communications Technology adoption in Bangladeshi higher education remains uneven. Public universities in rural areas face infrastructure gaps, unstable internet, and power shortages, while private urban institutions perform better. Faculty lack Information and Communications Technology training and motivation, and students experience sharp digital, economic, and gender disparities. COVID-19 accelerated Information and Communications Technology use but exposed existing inequalities. Novelty/Originality of this study: This study uniquely connects Information and Communications Technology integration with issues of equity, regional disparity, and pedagogical readiness in Bangladesh. It advances knowledge by highlighting how digital transformation can promote inclusive higher education and strengthen national competitiveness in the emerging knowledge economy.